Nucleotide variability of Tahyna virus (Bunyaviridae, Orthobunyavirus) small (S) and medium (M) genomic segments in field strains differing in biological properties - Kilian, Patrik; Růžek, Daniel; Danielová, Vlasta; Hypša, Václav; Grubhoffer, Libor (Virus research, 2010)
Tahyna virus (TAHV), a mosquito-borne bunyavirus (California group), is frequently associated with inapparent or influenza-like (Valtice fever) infections in humans, rarely leading to atypical pneumonia or meningitis. Field TAHV strains exhibit a high variability in their biological properties with respect to virulence for laboratory mouse, temperature-sensitivity or character of plaques in cell culture. In consideration of the variations in the antigenic properties TAHV and its potential genetic variability, we analyzed complete nucleotide sequences of the small (S) and medium (M) genomic segments of field TAHV strains with different combinations of phenotypic markers. S segment was highly conservative in all analyzed TAHV strains. Within the M segment, the highest variability was observed in the G(C) gene encoding viral envelope protein and to a less extent also in the NSm gene. However, 5' and 3' non-coding regions of M segment, as well as in G(N) gene exhibited highly conservative pattern, indicating its functional importance, but minor or no role in the determination of biological properties of TAHV field strains.
Keywords: Virulence; Animals; 5' nepřekládaná oblast; Genome, Viral; viry kalifornské encefalitidy; sekvenční homologie; vysoká teplota; Viral Envelope Proteins; Viral Plaque Assay; Hot Temperature; genom virový; Encephalitis Virus, California; RNA, Viral; shluková analýza; lidé; Molecular Sequence Data; 3' nepřekládaná oblast; Mice; 3' Untranslated Regions; myši; Sequence Homology; kalifornská encefalitida; Genetic Variation; RNA virová; virulence; Phylogeny; proteiny virového obalu; molekulární sekvence - údaje; 5' Untranslated Regions; konzervovaná sekvence; plakové testy; Sequence Analysis, DNA; zvířata; sekvenční analýza DNA; Cluster Analysis; fylogeneze; genetická variace; Encephalitis, California; Conserved Sequence; Humans